Assessment of genetically modified soybean MON 87751 × MON 87701 × MON 87708 × MON 89788 for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2016‐128). (11th November 2019) - ; Naegeli, Hanspeter; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Mullins, Ewen; Nogué, Fabien; et al.
Abstract: Soybean MON 87751 × MON 87701 × MON 87708 × MON 89788 (four‐event stack soybean) was produced by conventional crossing to combine four single events: MON 87751, MON 87701, MON 87708 and MON 89788. The GMO Panel previously assessed the four single events and did not identify safety concerns. No new data on the single events have been identified that would lead to modification of the original conclusions on their safety. The molecular characterisation, comparative analysis (agronomic, phenotypic and compositional characteristics) and the outcome of the toxicological and allergenicity assessment indicate that the combination of the single soybean events and of the newly expressed proteins in the four‐event stack soybean does not give rise to food and feed safety and nutritional concerns. The GMO Panel concludes that the four‐event stack soybean, as described in this application, is as safe as and nutritionally equivalent to the non‐GM comparator and the non‐GM reference varieties tested. In the case of accidental release of viable seeds of the four‐event stack soybean into the environment, this would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of the four‐event stack soybean. Post‐market monitoring of food/feed is not considered necessary. The GMO Panel concludes that the four‐event stack soybean is as safe as the non‐GM comparator and the tested non‐GM reference varieties with respect to potential effects on human and animal health and the environment.